Forage mass and nutritional value of elephant grass intercropped with forage legumes - Seibt, Daiane Cristine; Olivo, Clair Jorge; Alessio, Vinicius; Paim Sauter, Caroline; Bratz, Vinicius Felipe; Flôres Aguirre, Priscila (Revista Ceres, 2025)
Forage-legume systems are a sustainable and competitive alternative for improving pasture yield and quality because of the symbiotic nitrogen fixation capacity and high nutritional value of legumes. This study aimed to evaluate the forage mass, nutritional value, and nutrient export rate in three forage systems (FS): FS1, with elephant grass (Pennisetum purpureum) (EG), annual ryegrass (Lolium multiflorum) (AR), and spontaneous growth species (SGS); FS2, with EG + AR + SGS + arrowleaf clover (Trifolum vesiculosum); and FS3, with EG + AR + SGS + forage peanut (Arachis pintoi). The experiment was arranged in a completely randomized design, with three replicates, and repeated measures over time. Results of pre-grazing forage mass were 3.5, 3.8, and 3.9 t/ha, and crude protein export were 1.4, 2.1, and 2.3 t/ha, for the treatments FS1, FS2 and FS3, respectively. Highest crude protein, in situ dry matter digestibility and total digestible nutrients, and lowest neutral detergent fiber were found in the intercropping system with forage peanut, especially in winter. Nutritional values were also better in legume-systems than the non-legume system.